2017
DOI: 10.1111/plb.12642
|View full text |Cite
|
Sign up to set email alerts
|

Physiological dissection revealed that both uptake and assimilation are the major components regulating different growth responses of two tobacco cultivars to nitrogen nutrition

Abstract: K326 and HD represent major tobacco cultivars in China, which required large N fertiliser input but at different application rates. To understand primary components affecting tobacco N use physiology, we adopted these two varieties as valuable genetic material to assess their growth response to N nutrition. We established a hydroponic culture system to grow plants supplied with different N regimes. Plant biomass, N, ammonium, nitrate, arginine, GS and NR activity, N transfer and use efficiency as well as root … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 52 publications
2
17
0
Order By: Relevance
“…In this work, we revealed that cotton roots preferentially absorb ammonium when presented equimolarly with nitrate in the medium (Fig. A), despite being an unfavorable N‐source for the growth of some crops, including cotton plants, when grown solely with NH 4 + as N form (Gerendás et al , Britto and Kronzucker , Fan et al ). Subsequently, we have for the first time provided kinetic evidence for cotton NH 4 + acquisition.…”
Section: Discussionmentioning
confidence: 80%
“…In this work, we revealed that cotton roots preferentially absorb ammonium when presented equimolarly with nitrate in the medium (Fig. A), despite being an unfavorable N‐source for the growth of some crops, including cotton plants, when grown solely with NH 4 + as N form (Gerendás et al , Britto and Kronzucker , Fan et al ). Subsequently, we have for the first time provided kinetic evidence for cotton NH 4 + acquisition.…”
Section: Discussionmentioning
confidence: 80%
“…Indeed, Poorter et al [25] relate the challenge of assessing a reliable mass of roots in plants conducted in pot experiments with substrate. Fan et al [15] found a decrease of root/shoot ratio with increasing N concentration for one cultivar, but not in another one when supplied solely with N-NO 3 . However, our data are in accordance with the "functional equilibrium" existing between roots and shoots described by Brouwer [26].…”
Section: Variation Of N Utilization Efficiency (Nue) Traits Among Genmentioning
confidence: 95%
“…For tobacco genotypes, few works have used numerous genotypes in the study of NUE traits [13,14]. Thus, studies of the mechanisms behind NUE traits are limited to a few tobacco genotypes [15,16]. Again, this is comprehensive, since the growing process of many genotypes is time-intensive in terms of labor, and plant analysis is frequently time consuming with associated high costs (e.g., physiological analysis, 15 N isotypes).…”
Section: Introductionmentioning
confidence: 99%
“…Plants show great genetic variation in nitrogen uptake, translocation and assimilation, and in conversion of the assimilated products into amino acids and other nitrogen‐containing compounds, which results in distinct responses in nitrogen and amino acid contents to nitrogen fertilization among plant species . For example, tobacco K326 has higher foliar nitrogen content under nitrate fertilization than tobacco HD, which is due to the higher activity of nitrate reductase and nitrite reductase . Thus, insects feeding on the different plants could have various responses to nitrogen fertilization .…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] For example, tobacco K326 has higher foliar nitrogen content under nitrate fertilization than tobacco HD, which is due to the higher activity of nitrate reductase and nitrite reductase. 11 Thus, insects feeding on the different plants could have various responses to nitrogen fertilization. 12 Moreover, the existence of an optimal plant nitrogen level for herbivorous insects has been proposed, and this differs among insect species.…”
Section: Introductionmentioning
confidence: 99%